Healthy homes: Stakeholder perspectives on housing interventions to reduce environmentally mediated infections. - Matthias Acklin; Jay P Graham; Jade Benjamin-Chung (PLOS Global Public Health)
Housing conditions are intrinsically linked to human health, with inadequate housing potentially increasing exposure to environmentally mediated pathogens. Beyond efforts to improve water and sanitation and reduce household air pollution, housing improvements remain relatively under-explored as health interventions. This study explored facilitators of and barriers to funding, implementing, and scaling up of housing improvements as health interventions to reduce environmentally mediated infectious diseases. Sixteen key informants (KIs) with direct experience conducting housing interventions with a goal to reduce environmentally mediated infectious diseases in low- and middle-income countries were interviewed using a semi-structured interview format. KIs had diverse backgrounds, including academics researching housing interventions, housing policy advisors, and practitioners implementing housing interventions. A thematic analysis approach was used to identify key themes in interview transcripts, highlighting patterns, commonalities, and variations in participants' responses. KIs emphasized that housing interventions can deliver across a broad set of health outcomes, including physical and mental health, as well as environmental, social, and economic dimensions. Funding and financial mechanisms to address housing interventions were highlighted as key barriers, alongside the need to provide more rigorous evidence and cost-benefit analyses for housing interventions. KIs indicated that funding limitations were likely driven by a deficiency in awareness regarding the significance of housing among decision-makers, and suggested that efforts are needed to foster more intersectoral collaboration. The interviews also revealed a need for more context-specific housing policies and a need to contextualize interventions to their specific setting in order to foster community involvement and successful implementation and scale-up. Housing interventions play a pivotal role in mitigating many environmentally mediated diseases. By integrating these interventions with existing programs, such as water and sanitation or efforts to reduce household air pollution, there is the potential to create a more comprehensive approach to healthy housing in the face of climate change.